POOL BOILING IN HIGHLY VISCOUS MIXTURES - DESIGN OF A NEW APPARATUS AND RESULTS OF PRETESTS - Span, R.; Gerber, M.; Buljina, I.; Baumhögger, Elmar (Boiling)

Systemanalyse im Unternehmen - Prozessorientierte Methoden der Wirtschaftsinformatik

Virtual Knowledge Communities - IT-supported Visualization and Analysis - Trier, Matthias

Systemanalyse zur Verbesserung von Geschäftsprozessen - Aier, Stephan; Haarlaender, Nico (Systemanalyse im Unternehmen : Prozessorientierte Methoden der Wirtschaftsinformatik)

Generische Transformation von Learning-Content - Das MOCCA-Projekt - Herzog, Michael A.; Trier, Matthias (Proceedings Wirtschaftsinformatik 2007)

Towards Understanding the Dynamics of Digital Communication Networks - Trier, Matthias; Bobrik, Annette; Bartels, Tilmann (Proceedings Wirtschaftsinformatik 2007)

Ein Ansatz zur prozessorientierten Evaluation von Learning Management Systemen - Luther, Michael; Trier, Matthias (Proceedings Wirtschaftsinformatik 2007)

IRIS (1978-2006) Historical Reflection through Visual Analysis - Molka-Danielsen, Judith; Trier, Matthias; Shlyk, Vadim; Bobrik, Annette; Nurminen, Markku I. (Proceedings of IRIS30, Tampere, 2007)
IRIS (Information Systems Research in Scandinavia) Conference is an annual meeting for researchers in Scandinavia. Through 29 annual conference meetings a social network of co-authorships and general research collaboration has emerged. This article contributes a historical reflection and analysis of the social network of researchers associated with the IRIS in the period from 1978 to 2006. We make use of the network visualization and analysis tool called Commetrix. We will examine the influence of certain researchers in this network by identifying their betweenness centrality and degree centrality. We will reflect on the nature and characteristic of the research topics by analyzing the network of keywords found in the conference paper titles, and visualizing their representation in the network.

Content und Kommunikation: Von der Dichotomie zur Kombination - Trier, Matthias (Content Engineering)

Systemanalyse im Wissensmanagement - Trier, Matthias; Bobrik, A. (Systemanalyse im Unternehmen - Prozessorientierte Methoden der Wirtschaftsinformatik)